Prevalence of Anti-neural Autoantibodies in a Psychiatric Patient Cohort-Paradigmatic Application of Criteria for Autoimmune-Based Psychiatric Syndromes - Hansen, Niels; Juhl, Aaron Levin; Grenzer, Insa Maria; Rentzsch, Kristin; Wiltfang, Jens; Fitzner, Dirk (Frontiers in Psychiatry, 2022)
Background: Anti-neural autoantibodies associated with psychiatric syndromes is an increasing phenomenon in psychiatry. Our investigation aimed to assess the frequency and type of neural autoantibodies associated with distinct psychiatric syndromes in a mixed cohort of psychiatric patients. Methods: We recruited 167 patients retrospectively from the Department of Psychiatry and Psychotherapy, University Medical Center Göttingen for this study. Clinical features including the assessment of psychopathology via the Manual for Assessment and Documentation of Psychopathology in Psychiatry (AMDP), neurological examination, cerebrospinal fluid (CSF), magnetic resonance imaging (MRI) and electroencephalography (EEG) analysis were done in patients. Serum and or CSF anti- neural autoantibodies were measured in all patients for differential diagnostic reasons. Results: We divided patients in three different groups: (1) psychiatric patients with CSF and/or serum autoantibodies [PSYCH-AB+, n=25 (14.9%)], (2) psychiatric patients with CSF autoantibodies [PSYCH-AB CSF+, n=13 (7.8%)] and (3) those psychiatric patients without autoantibodies in serum and/or CSF [PSYCH-AB-, n=131]. The prevalence of serum neural autoantibodies was 14.9% (PSYCH-AB+), whereas 7.2% had CSF autoantibodies (PSYCH-AB CSF+) in our psychiatric cohort. The most prevalent psychiatric diagnoses were neurocognitive disorders (61-67%) and mood disorders (25-36%) in the patients presenting neural autoantibodies (PSYCH-AB+ and PSYCH-AB CSF+). However, psychiatric diagnoses, neurological deficits, and laboratory results from CSF, EEG or MRI did not differ between the three groups. To evaluate the relevance of neural autoantibody findings, we applied recent criteria for possible, probable, or definitive autoimmune based psychiatric syndromes in an paradigmatic patient with delirium and in the PSYCH-AB+ cohort. Applying criteria for any autoimmune-based psychiatric syndromes, we detected a probable autoimmune-based psychiatric syndrome in 13 of 167 patients (7.8%) and a definitive autoimmune-based psychiatric syndrome in 11 of 167 patients (6.6%). Conclusions: Neural autoantibodies were detected mainly in patients presenting neurocognitive and mood disorders in our psychiatric cohort. The phenotypical appearance of psychiatric syndromes in conjunction with neural autoantibodies did not differ from those without neural autoantibodies. More research is therefore warranted to optimize biomarker research to help clinicians differentiate patients with potential neural autoantibodies when a rapid clinical response is required as in delirium states.